MicroRNA‐202 safeguards meiotic progression by preventing premature SEPARASE‐mediated REC8 cleavage. (17th June 2022) - Chen, Jian; Gao, Chenxu; Luo, Mengcheng; Zheng, Chunwei; Lin, Xiwen; Ning, Yan; Ma, Longfei; He, Wei; Xie, Dan; Liu, Kui; Hong, Kai; Han, Chunsheng
Abstract: MicroRNAs (miRNAs) are believed to play important roles in mammalian spermatogenesis but the in vivo functions of single miRNAs in this highly complex developmental process remain unclear. Here, we report that miR‐202, a member of the let‐7 family, plays an important role in spermatogenesis by phenotypic evaluation of miR‐202 knockout (KO) mice. Loss of miR‐202 results in spermatocyte apoptosis and perturbation of the zygonema‐to‐pachynema transition. Multiple processes during meiosis prophase I including synapsis and crossover formation are disrupted, and inter‐sister chromatid synapses are detected. Moreover, we demonstrate that Separase mRNA is a miR‐202 direct target and provides evidence that miR‐202 upregulates REC8 by repressing Separase expression. Therefore, we have identified miR‐202 as a new regulating noncoding gene that acts on the established SEPARASE‐REC8 axis in meiosis. Synopsis: miR‐202 maintains chromosomal synapsis during meiosis I in males by preventing premature REC8 cleavage by SEPARASE that is targeted by miR‐202‐3p . miR‐202 depletion results in spermatocyte apoptosis and perturbation of the zygonema‐to‐pachynema transition. miR‐202 KO mice exhibit multiple synapsis defects including inter‐sister synapsis. Meiosis‐specific cohesin REC8 is prematurely cleaved in miR‐202 KO mice. Separase mRNA is a direct target of miR‐202‐3p . Abstract : miR‐202 maintains chromosomal synapsis during meiosis I in males by preventing premature REC8 cleavage by SEPARASE that is targeted by miR‐202‐3p .